Решить уравнения: 7(1-х) = (2х+3)(1-х) |х²-4| = 3

Илий Илий    1   19.05.2019 06:30    1

Ответы
sultanguloverik2 sultanguloverik2  12.06.2020 11:01
7-7х = 2х-2х^2+3-3х
2х^2-6х+4=0 | разделим все на 2
х^2-3х+2=0
D=9-4*2
D=1
x1=(3+1)/2=2
x2=(3-1)/2=1

x^2-4=3
x^2=7
x=+ и - корень из 7

-х^2+4=3
-х^2=-1
х^2=1
х= + и - 1
ПОКАЗАТЬ ОТВЕТЫ
Сабусик12 Сабусик12  12.06.2020 11:01

7(1-x)=(2x+3)(1-x) 

7-7x=2x-2x²+3-3x

-7x-2x+2x²+3x=3-7

-6x+2x²=-4

-4x²=-4

x²=-4:-4

х²=1

 

 

 

 

 

 

 

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра